Analisis Kebijakan Karir Tenaga Pendidik - Putra, Windisyah (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2024)
Educational policies need to be continuously monitored and evaluated due to their crucial role. Various interrelated factors, such as communication, resources, disposition, and structure, influence the implementation of these policies. Implementation can occur hierarchically, from top to bottom, by applying managerial and political procedures and approaches. Analyzing the career policies of educators in Indonesia highlights the challenges and opportunities faced in their implementation. Despite the allocation of 20% of the state budget (APBN) to education, its effectiveness remains questionable due to government disagreements and low teacher qualifications, as reflected in the results of the Teacher Competency Test (UKG), which are below standard. Data indicates that many teachers lack qualifications in pedagogical and professional competencies, negatively impacting education quality and student engagement. This study employs a descriptive qualitative method to explore related issues and gather information from various literature sources. The findings emphasize the need for teacher development and better career advancement strategies to enhance professionalism and the well-being of educators. Thus, this research recommends a holistic and collaborative approach to educational policy to achieve the desired quality.